Development of carbon fiber/phenolic resin prepregs modified with nanoclays. (May 2016) - Asaro, L; Rivero, G; Manfredi, LB; Alvarez, VA; Rodriguez, ES
This work is focused on the study of the main variables involved in the development of phenolic/carbon prepregs and how these variables are affected by the incorporation of nanoclays. For this, phenolic resin was obtained from phenol and formaldehyde, performing the reaction under basic conditions and with formaldehyde excess. Resin curing kinetics was studied by means of Fourier transform infrared spectroscopy measurements. Organo-modified clay was added to the phenolic resin in order to evaluate their effect on the general performance of the material. Carbon fiber/phenolic resin and carbon fiber/clay modified phenolic resin prepregs were obtained by hand-layup and vacuum bagging. Prepregs were characterized in terms of fiber content, flexural stiffness, and degree of tack. In both the cases, intermediate fiber volume content, nearly 50%, was obtained. The addition of 5 wt% of clay to the phenolic resin did not produce a significant change on the prepregs stiffness but increased the degree of tack, which implies that the incorporation of such particles was useful to enhance the prepregs properties. Composite materials were obtained by compression molding of the prepregs obtained, and were characterized by its fiber content, mechanical behavior with the three-point bending test and its thermal degradation by thermogravimetry. High fiber content composites materials were obtained, nearly 75% by volume. However, modified composites showed lower fiber content, which resulted in a decrease of the flexural modulus and strength. In relation to thermal degradation, the addition of nanoclay did not change the behavior of the materials.